Critical success factors model (CSF’sM) affecting the competencies of civil engineer in construction project - Ismail, Hassan (2020)
Highly skilful and competent civil engineers are required to accelerate and contribute effectively to technology development in spearheading Malaysia’s transformation agendas. The competency of these engineers included a combination of technical and thinking skills (intelligences), knowledge and experience, and willingness to conduct specified job tasks and work in compliance with agreed standards, rules and procedures. The aim of this research is to establish the critical success factors models (CSF’sM) affecting competencies of civil engineers in a construction project as well as to help improve managerial performance on the successful completion of construction project. Quantitative research method has been adopted in this study and the main survey using structured questionnaires. The questionnaire consisted of 53 critical success factors and 10 engineering competencies skills. The critical success factors (Independent Variable) is clustered into 5 groups and all the engineering competencies skills (Dependent Variable) is clustered in 1 group. These factors and assigned groups were validated by 33 construction personnel (directors, managers and engineers) during a pilot study. The main survey was conducted with a total of 360 questionnaires were received from civil engineers who work in G7 grade contractor registered with the Construction Industry Development Board (CIDB) and only involved the states of Johor, Selangor and Federal Territory of Kuala Lumpur by respond rate of 60%. The results from the survey were analysed using descriptive analysis and factor analysis. Next, the data analysis is carried out using SmartPLS software. A structural model of critical success factors affecting competencies of civil engineer was developed using Partial Least Squared-Structural Equation Modelling (PLS-SEM) technique. It was found that the model is fit due to the R2 value = 0.502 and in line with expert’s validation results. The model identifies that all 5 groups (Interpersonal Skills, Project Integration Management, Project Human Resource Management, Project Communication Management and Project Risk Management) are significant with t-value ≥ 1.645. Finally, this finding was validated by 11 construction practitioners who agreed that ‘Interpersonal skills’ group of factors contributes the highest impact on critical success factors affecting competencies of Civil Engineer in construction project. It is important that Civil Engineer should have knowledge and skills in term of management and technical skill. Therefore, Civil Engineer should improve their personal knowledge management skills in order to help their project team develop and implement project management knowledge and skills for their construction project in future.